2016
DOI: 10.1093/occmed/kqv164
|View full text |Cite
|
Sign up to set email alerts
|

A review of occupational physical activity and sedentary behaviour correlates

Abstract: Intervention efforts to increase occupational physical activity and reduce sedentary time may be most effective when targeted at white-collar workers. Research is needed to identify additional modifiable correlates of occupational physical activity and sedentary behaviour, in white-collar workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
2
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(100 citation statements)
references
References 61 publications
1
90
2
7
Order By: Relevance
“…Such previous systematic review evidence (that included self-report and device-measured outcomes) identified that white-collar workers (e.g. desk-based professionals) were more likely to engage in higher amounts of occupational ST and lower levels of occupational PA [20]. White-collar workers have also been shown engage in higher leisure-time PA compared to blue-collar workers [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such previous systematic review evidence (that included self-report and device-measured outcomes) identified that white-collar workers (e.g. desk-based professionals) were more likely to engage in higher amounts of occupational ST and lower levels of occupational PA [20]. White-collar workers have also been shown engage in higher leisure-time PA compared to blue-collar workers [18].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the research examining occupational PA has been measured using self-report tools (e.g. questionnaires) [20], introducing considerable measurement errors (i.e. social desirability, recall bias, poor validity) [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reviews have identified that blue collar workers report higher levels of occupational PA and lower levels of leisure time PA than white collar and professional workers [11,40]. However, in the current study, after adjusting for covariates, it was not the ‘blue collar’ (used to describe the trades/production/labourer category in this study) workers, but the clerical/sales workers, who were significantly less likely to be physically active, when compared with managers/professionals in the young cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we hand‐searched articles on the Sedentary Behaviour Research Network website (https://www.sedentarybehaviour.org/) and checked reference lists of relevant reviews . Furthermore, we requested for relevant studies on social media platforms; ResearchGate (social media network for scientists) and Twitter.…”
Section: Methodsmentioning
confidence: 99%
“…We performed searches in the following scientific databases: Medline org/) and checked reference lists of relevant reviews. 32,34,35,40,[46][47][48][49][50] Furthermore, we requested for relevant studies on social media platforms; ResearchGate (social media network for scientists) and Twitter. This allowed us to include studies until August 2019.…”
Section: Search Strategymentioning
confidence: 99%